Analysis of Fraudulent Behavior using the Fraud Hexagon Approach at Jambi University - Hulu, Grecia Febnasdi Rahelia; Iskandar Sam; Misni Erwati (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to determine and analyze fraudulent behavior using the fraud hexagon approach at Jambi University. The fraud hexagon used in this research consists of several factors, namely pressure, opportunity, rationalization, ability, arrogance, and collusion. This research uses quantitative and descriptive research methods. The type of data used is primary data collected using a questionnaire from 106 respondents who are leaders and employees whose scope of work is in the finance and procurement of goods/services at Jambi University. The results of this research show that if fraudulent behavior occurs at Jambi University, the most dominant factor in the fraud hexagon is the pressure factor